2023
DOI: 10.1108/k-11-2022-1532
|View full text |Cite
|
Sign up to set email alerts
|

Spatial correlation and influencing factors of the urban land transaction market in the Yangtze River Delta urban agglomeration

Abstract: PurposeLand transactions are a key indicator of urban sustainable development and urban space expansion. Therefore, this paper aims to study the spatial correlation of different types of land transactions.Design/methodology/approachBased on the big data of land micro transactions in Yangtze River Delta urban agglomeration, this paper uses the generalized forecast error variance decomposition (GFEVD) method to measure the correlation level of urban land markets. Also, social network analysis (SNA) is used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Based on the development reality of the Yangtze River Delta, the main economic and social development indicators of the 14 th Five-Year Plan and previous research results [30,31], selected population size, economic scale, industrialization level, urbanization level, and energy intensity as the influencing factors and constructed an extended STIRPAT model for air pollution control and carbon reduction in the Yangtze River Delta; On this basis, the forecast analysis is further carried out from the two dimensions of synergistic emission equivalent and synergy coefficient. The following conclusions are drawn:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the development reality of the Yangtze River Delta, the main economic and social development indicators of the 14 th Five-Year Plan and previous research results [30,31], selected population size, economic scale, industrialization level, urbanization level, and energy intensity as the influencing factors and constructed an extended STIRPAT model for air pollution control and carbon reduction in the Yangtze River Delta; On this basis, the forecast analysis is further carried out from the two dimensions of synergistic emission equivalent and synergy coefficient. The following conclusions are drawn:…”
Section: Discussionmentioning
confidence: 99%
“…This study retains the original variables (population size and economic scale) of STIRPAT model. Referring to the research conducted by Jiang Huiqin et al [30] and Li Zhiqing et al [31], Industrialization level, urbanization level and Energy intensity are vital factors affecting the Co-benefits in the Yangtze River Delta in recent trends. Therefore, the finally chosen five variables as shown in Table 3.…”
Section: Factors Selection Of Stirpat Modelmentioning
confidence: 99%
“…Zhang Xianxian et al focused on cities in the Yangtze River Delta region and used spatial analysis methods to study the differences in urban tourism development. The results showed that the overall tourism development trend in the Yangtze River Delta was good, but regional differences were significant [7,8,9,10]. In the study of combining tourism development efficiency with spatial analysis, Yu Tingting and Zuo Bing [11] used the DEA model to evaluate the comprehensive efficiency, pure technical efficiency, and scale efficiency of various prefecture level cities.…”
Section: Introductionmentioning
confidence: 99%